A novel control algorithm for dephosphorization in an LD converter. (January 2015) - Tomiyama, Shinji; Uchida, Yuichi; Mizuno, Hiroshi; Akiu, Kengo; Maeda, Takahiko
Highlights: A new control algorithm for dephosphorization in steel refining process is proposed. The algorithm creates control inputs based on past operation data instead of a complex process model. The algorithm includes techniques of instance-based learning and independent component analysis. Experimental results show that the algorithm improves performance of dephosphorization control. Abstract: This paper proposes a new control algorithm for dephosphorization in the steelmaking process using a LD converter. The control algorithm is composed of two steps, which achieves a low phosphorous content in the hot metal after treatment. The first step creates target concentration for the iron oxide in the slag for the next heat, which is optimal to achieve effective dephosphorization. The target concentration is obtained after applying independent component analysis (ICA) to the concentration data of past heats. The second step decides the control inputs for the next heat, namely the oxygen blowing rate and the lance height by calculating a weighted summation of past control inputs. The weight is based on the difference between the target concentration and concentration of each past heat. The proposed algorithm was applied to an actual process, and the results showed high control performance at the end of this paper.